2009
DOI: 10.2215/cjn.02620409
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Dietary, and Urinary Factors and 24-h Urinary Calcium Excretion

Abstract: Conclusions: Intestinal calcium absorption and/or negative calcium balance is greater in SF than NSF. Higher calcium intakes at levels typically observed in free-living individuals are associated with only small increases in urinary calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 45 publications
7
47
3
3
Order By: Relevance
“…Of note, we previously reported that the magnitude of the independent association between calcium intake and urinary calcium in our study population was small (25). Our urinary calcium results are consistent with data from the initial trial examining the effect of the DASH diet on blood pressure (3).…”
Section: Discussionsupporting
confidence: 89%
“…Of note, we previously reported that the magnitude of the independent association between calcium intake and urinary calcium in our study population was small (25). Our urinary calcium results are consistent with data from the initial trial examining the effect of the DASH diet on blood pressure (3).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, participants' 24-h urinary phosphate excretion was only ∼700 mg/day at baseline, or ∼30% lower than the level we expected based on studies of individuals with normal kidney function consuming an American diet [25]. Furthermore, one patient who received the 1500-mg diet plus placebo developed new-onset hyperphosphataemia.…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that calcium intakes within normal ranges, unlike salt and proteins, does not promote hypercalciuria (23,24). Higher dietary calcium has even been associated to a lower risk of kidney stones (25).…”
Section: Discussionmentioning
confidence: 99%